Przestrzeganie zasady jawności postępowania sądowego w Polsce podczas stanu epidemii COVID-19. Wyniki badań empirycznych - Pilitowski, Bartosz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The article concerns the principle of open court, which is an important part of the right to a fair trial under the Constitution of the Republic of Poland and international treaties. It discusses the legal basis and exceptions to the principle of open court and its importance from the sociological perspective as an institution of social control. Next, the author discusses the results of empirical research on the practical observance of the open court principle during the state of epidemic. Orders of court presidents regulating access to court buildings and observation of court sessions are analysed. Finally, the author compares the reactions of judges to the observed threats to the principle of open court and compares them with the reactions to threats to other elements of the right to a fair trial. He discusses possible conclusions that can be drawn from the results of these studies for understanding the changes in the value system of the professional group of judges in Poland.